2007
DOI: 10.1213/01.ane.0000261517.27532.80
|View full text |Cite
|
Sign up to set email alerts
|

Do Surgical Patients Benefit from Perioperative Gabapentin/Pregabalin? A Systematic Review of Efficacy and Safety

Abstract: Gabapentinoids effectively reduce postoperative pain, opioid consumption, and opioid-related adverse effects after surgery. Conclusions about the optimal dose and duration of the treatment cannot be made because of the heterogeneity of the trials. Studies are needed to determine the long-term benefits, if any, of perioperative gabapentinoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
269
2
25

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(305 citation statements)
references
References 53 publications
9
269
2
25
Order By: Relevance
“…Pregabalin has analgesic, anticonvulsant, and anxiolytic effects [5,6]. Several studies have demonstrated the efficacy of oral pregabalin on post-operative analgesia and reduction of parenteral analgesics [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Pregabalin has analgesic, anticonvulsant, and anxiolytic effects [5,6]. Several studies have demonstrated the efficacy of oral pregabalin on post-operative analgesia and reduction of parenteral analgesics [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It also had a longer duration of analgesia than ibuprofen Stahl, [33] . In 2007 Tippana et al [34] analyzed 22 randomized, controlled trials examining the analgesic efficacy, adverse effects, and clinical value of gabapentinoids (pregabalin and gabapentin) in postoperative pain. They concluded that gabapentinoids effectively reduce postoperative pain, opioid consumption, and opioid-related side effects after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While shown to be effective analgesics, both non-selective and COX-2 selective nonsteroidal anti-inflammatory drugs (NSAIDs) have potentially serious risks in this surgical group. 7,8 The alpha-2-delta ligand drugs, gabapentin and pregabalin, have been shown to reduce pain scores and opioid requirements and to improve postoperative pulmonary function in a number of surgical settings 9,10 To date, there have been no published reports on the use of these drugs in the setting of cardiac surgery.…”
Section: Résumémentioning
confidence: 99%